2007
DOI: 10.1016/j.brainres.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide mediates cerebral vasodilatation during acute hypertension

Abstract: Parasympathetic nerves from the pterygopalatine ganglia provide nitroxidergic innervation to forebrain cerebral blood vessels. Disruption of that innervation attenuates cerebral vasodilatation seen during acute hypertension as does systemic administration of a non-selective nitric oxide synthase (NOS) inhibitor. Although such studies suggest that nitric oxide (NO) released from parasympathetic nerves participates in vasodilatation of cerebral vessels during hypertension that hypothesis has not been tested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 44 publications
3
34
1
Order By: Relevance
“…␤-Adrenoceptors and nNOS-derived NO seem to interact in contributing to hypoglycemia-induced cerebral vasodilatation, and the vasodilating signal may be transmitted via a neuronal pathway. In anesthetized rats, without the nNOS inhibitor propyl-L-arginine, the pial arterial diameter abruptly increased when mean arterial pressure rose, whereas with nNOS inhibition the diameter increased to a much lesser extent even when arterial pressure was similarly raised; the nNOS inhibitor attenuated pial arterial dilatation induced by NMDA but not that induced by ACh delivered into a cranial window (Talman and Nitschke Dragon, 2007). NO released from parasympathetic fibers seems to contribute to cerebral vasodilatation during acute hypertension.…”
Section: Involvement Of Neurogenic Nitric Oxide In Diseasesmentioning
confidence: 87%
See 1 more Smart Citation
“…␤-Adrenoceptors and nNOS-derived NO seem to interact in contributing to hypoglycemia-induced cerebral vasodilatation, and the vasodilating signal may be transmitted via a neuronal pathway. In anesthetized rats, without the nNOS inhibitor propyl-L-arginine, the pial arterial diameter abruptly increased when mean arterial pressure rose, whereas with nNOS inhibition the diameter increased to a much lesser extent even when arterial pressure was similarly raised; the nNOS inhibitor attenuated pial arterial dilatation induced by NMDA but not that induced by ACh delivered into a cranial window (Talman and Nitschke Dragon, 2007). NO released from parasympathetic fibers seems to contribute to cerebral vasodilatation during acute hypertension.…”
Section: Involvement Of Neurogenic Nitric Oxide In Diseasesmentioning
confidence: 87%
“…Erythrocyte velocity in rat cerebral capillaries increased, as arterial hematocrit was reduced; pretreatment with 7-NI abolished the increase in velocity, leading to the conclusion that NO from a neural source may contribute to the increase in capillary erythrocyte flow during hemodilution . There was evidence suggesting that NO released from parasympathetic fibers contributes to cerebral vasodilatation during acute hypertension in anesthetized rats (Talman and Nitschke Dragon., 2007). On the other hand, Stefanovic et al (2007) found that 7-NI had no effect on cerebral blood flow in anesthetized rats.…”
Section: In Vivo Studies a Basal Release Of Nitric Oxidementioning
confidence: 99%
“…The role of nNOS-derived nitric oxide in cerebral vasodilatation in rats has been determined [47][48][49]. Pial artery diameter in rats increased when mean arterial pressure was raised, and this effect was inhibited by the nNOS inhibitor propyl-L-arginine; vasodilatation induced by NMDA, but not by ACh, was attenuated by the nNOS inhibitor [50]. The authors suggested that nitric oxide released from parasympathetic nitrergic nerves participates in cerebral vasodilatation during acute hypertension.…”
Section: Systemic Blood Pressure Regulation By Neurogenic Nitric Oxidementioning
confidence: 99%
“…Extrinsic innervation of arterial vessels seems not to be involved, as demonstrated by the preservation of autoregulation in sympathetically and parasympathetically denervated animals [24]. On the other hand, intrinsic innervation may be involved, as well as metabolic modulation through the release of nitric oxide, adenosine and other vasoactive substances [25,26].…”
Section: Autoregulation Of Cerebral Blood Flowmentioning
confidence: 99%